Symptom characteristics of depressive episodes prior to the onset of mania or hypomania. (7th August 2015) - Pfennig, A.; Ritter, P. S.; Höfler, M.; Lieb, R.; Bauer, M.; Wittchen, H.‐U.; Beesdo‐Baum, K.
Abstract : Objective: Depressive episodes are typically the initial presentation of bipolar disorder. The evidence as to whether depressive episodes occurring in persons who later convert to bipolar disorder are symptomatically distinct from episodes of unipolar depression remains controversial. As there are crucial differences in the therapeutic management, symptom profiles indicating subsequent bipolar conversion may aid in appropriate treatment. Method: A representative community sample of originally N = 3021 adolescents and young adults aged 14–24 years at baseline was assessed up to four times over 10 years. Assessment of symptoms was conducted by clinically trained interviewers using the standardized M‐CIDI. Symptom profiles of depressive episodes were compared via logistic regression between subjects that subsequently developed (hypo‐)manic episodes ( n = 35) or remained unipolar depressive ( n = 659). Results: Initial depression amongst prospective converters was characterized by significantly increased suicidality (odds ratio, OR = 2.31), higher rates of feelings of worthlessness and excessive guilt (OR = 2.52), complete loss of pleasure (OR = 2.53) and diurnal variation (OR = 4.30). No differences were found for hyperphagia, hypersomnia and psychomotor alterations. Conclusion: Findings suggest that the symptom profile of initial depressive episodes may be useful in the identification of subjects with an elevated risk for the subsequent conversion to bipolar disorder.